2016
DOI: 10.15171/ps.2016.11
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil Compositions of Malaysian Lauraceae: A Mini Review

Abstract: Introduction The Lauraceae family is by far the largest family of the order Laurales with about 50 genera and over 2000 species distributed throughout tropical to subtropical latitudes especially in Southeast Asia and tropical America. 1 Several genera have a pantropical distribution such as Beilschmiedia, Cassytha, Cryptocarya, Litsea, Ocotea, and Persea. Others are restricted to Asia and Australia which are Alseodaphne, Dehaasia, Endiandra, Eusideroxylon, Hexapora, and Neolitsea. Eusideroxylon is restricted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 24 publications
0
13
0
2
Order By: Relevance
“…Previous study on the essential oil of Cyathocalyx have been reported on Cyathocalyx zeylanicus collected from India (Hisham et al, 2012). In continuation of our systematic studies on pharmacologically active volatiles from Malaysian plants (Salleh et al,2014(Salleh et al, , 2015a(Salleh et al, , 2015b(Salleh et al, , 2016a(Salleh et al, , 2016b, we describe in this paper an evaluation of the chemical composition and acetylcholinesterase inhibitory activity of the essential oil from the leaf of C. pruniferus. Nat.…”
Section: Introductionmentioning
confidence: 78%
“…Previous study on the essential oil of Cyathocalyx have been reported on Cyathocalyx zeylanicus collected from India (Hisham et al, 2012). In continuation of our systematic studies on pharmacologically active volatiles from Malaysian plants (Salleh et al,2014(Salleh et al, , 2015a(Salleh et al, , 2015b(Salleh et al, , 2016a(Salleh et al, , 2016b, we describe in this paper an evaluation of the chemical composition and acetylcholinesterase inhibitory activity of the essential oil from the leaf of C. pruniferus. Nat.…”
Section: Introductionmentioning
confidence: 78%
“…Meanwhile, S. axillaris has not been previously studied for its essential oil. As a continuation part of our systematic evaluation of the aromatic flora of Malaysia (Salleh et al, 2014a(Salleh et al, , 2014b(Salleh et al, , 2014c(Salleh et al, , 2015(Salleh et al, , 2016a(Salleh et al, , 2016b(Salleh et al, , 2016c, we here report the volatile components of S. axillaris leaves. DOI: 10.37929/nveo.791343…”
Section: Introductionmentioning
confidence: 93%
“…Informasi ilmiah tersebut dapat berupa profil minyak atsiri yang terkait dengan gambaran mutunya, meliputi karakteristik, identifikasi kualitatif dan kuantitatif komponen penyusun hingga kemampuan bioaktif minyak atsiri tersebut dalam berbagai bidang. 17,18,19…”
Section: Pendahuluanunclassified